Agroforestry and land productivity: Evidence from rural Ethiopia - Geremew Worku Kassie (Cogent Food & Agriculture, 2016)
This study attempted to investigate the factors that substantiate the agroforestry adoption decisions of the farm households and its effect on farmland productivity. For the analysis of the agroforestry adoption incidences, the study employed probit model. The findings of the study indicated that being male-headed household, family size, vulnerability of the plot to land degradation, the comparative economic incentive of cash tree plantation and farm size have positive effect on cash tree adoption; while non-food crop farming practices and experience of cash-tree plantation had an adverse effect on the agroforestry plantation practices. Using OLS regression technique, farmland productivity was estimated, in contrast to a large body of theoretical and empirical literature, male-headed households were found to be less productive than female-headed counterparts. As projected, cash tree plantation bear out a positive impact on food crop productivity. This, in turn, empowered farm households to acquire and employ better farm technologies since cash tree plantation could enable rural Ethiopia farmers to fill the gap of rural financial market failures. Cash tree and agroforestry adoption among small farm households were also found to help farmers to improve and recover the rural farmland management system and to maximise the farm households’ productivity and income.